Comparison of efficacy and safety between aspirin and oral anticoagulants for venous thromboembolism prophylaxis after major orthopaedic surgery: a meta-analysis of randomized clinical trials - Zheng, Xingyue; Nong, Li; Song, Yujie; Han, Lizhu; Zhang, Yuan; Yin, Qinan; Bian, Yuan (Frontiers in Pharmacology, 2024)
Background: venous thromboembolism (VTE) is one of the most common complications after major orthopaedic surgery. Recent studies have suggested that aspirin may also be effective in preventing VTE, but it is still controversial whether it can be routinely used.To compare the efficacy and safety of aspirin against oral anticoagulants in the prevention of VTE following total hip arthroplasty (THA), total knee arthroplasty (TKA) or hip fracture surgery (HFS).Methods: Relevant publications have been obtained using electronic search databases such as PubMed, Embase, Web of Science, Cochrane Library, and Clinical Trials. gov. from inception to July 20, 2023. Only RCTs evaluating the efficacy and safety of aspirin compared with oral anticoagulants undergoing major orthopaedic surgery were included. The primary outcome reported was any VTE event. Secondary outcomes included mortality, major bleeding, minor bleeding, and wound complications. This is a provisional file, not the final typeset article Results: After screening 974 studies, 12 randomized clinical trials (RCTs) were included, involving 5088 participants. Aspirin was found to be less effective than oral anticoagulants in thromboprophylaxis after major orthopedic surgery. After subgroup analysis according to the type of oral anticoagulant, the results showed that aspirin was similar to rivaroxaban and inferior to warfarin. Considering that the studies in the warfarin group were all conducted before 2000, our results need to be further confirmed. In addition, the aspirin group had a higher risk of VTE than the control group in other subgroups, including a follow-up time of ≤3 months, type of procedure as TKA, high-dose aspirin (≥650 mg qd), and no combined use of mechanical prophylaxis. In terms of safety events, aspirin did not show significant differences in major bleeding, all-cause mortality, and wound-related events compared with oral anticoagulants, and aspirin was associated with a reduction in the risk of minor bleeding events and total bleeding.Aspirin reduces bleeding risk after major orthopedic surgery compared with oral anticoagulants, but may sacrifice VTE prevention to some extent. Updated evidence is needed to analyze the thromboprophylaxis effects of aspirin in patients undergoing major orthopedic surgery.